Industrial production as a credit driver in banking sector: An empirical study with wavelets - (:unkn) unknown (LLC CPC Business Perspectives, 2007)
This paper examines the timescale effects of industrial production on credits volume at banks. By using industrial production in Turkey and credit volumes of Turkish banks from 3/1992-12/2006, this study employs wavelet filters to estimate multi-scale causality for scaled time series. The original data is transformed by the wavelet filter up to 5 time scales. The first wavelet coefficient captures oscillations with a period length 3 to 6 months. Equivalently, the consequent wavelets capture oscillations with a period of 7-12, 13-24, 25-48 and 49-96 months, respectively. The results of multi-scale granger causality test show that the industrial production is effective on credits volume upto 24 months, while the credits volume starts to affect industrial production after 2 years. This paper has originality in presenting multi-scale effects of industrial production as a credit driver by using wavelet analysis with Turkish data. © Alper Ozun, Atilla Cifter, 2007.
Keywords: Bank credits; Granger causality; Industrial production; Multi-scale causality; Wavelets